PENGARUH EMPLOYEE ENGAGEMENT DAN WORK-LIFE BALANCE TERHADAP KEPUASAN KERJA KARYAWAN - Mandasari, Regina Aqilah; Irawanto, Dodi Wirawan (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to identify the effects of employee engagement and work-life balance on the job satisfaction of employees working at the Customer Service Unit of PT PLN (Persero) in Malang. This explanatory research corroborates the causal relationships between its variables through hypothesis testing. Using saturated sampling, all 72 employees of the said unit in Malang City were selected as the respondents. The research instruments were tested for validity and reliability, and the hypotheses were assessed using f test. The data was acquired via Likert-scaled questionnaires and analyzed in SPSS 26. This study finds that employee engagement partially does not influence the job satisfaction, but simultaneously it has significant effects. Then, work-life balance partially and simultaneously has significant effects on the employees’ job satisfaction.